Seed release in a changing climate: initiation of movement increases spread of an invasive species under simulated climate warming. Issue 6 (29th March 2016) - Teller, Brittany J.; Zhang, Rui; Shea, Katriona
Abstract: Aim: Reliable estimates of how species will move under future climatic conditions are lacking, and the ability of species to track suitable habitat under climate change is strongly predicated on dispersal. In wind‐dispersed plants, initiation of movement by maternal seed release characteristics can affect the ultimate shape of the dispersal kernel. If seed dispersal traits respond to altered local abiotic conditions induced by climate change during development, the effects could have major impacts on projections of future population spread. Location: Central Pennsylvania, USA. Methods: To quantify how seed release characteristics might be affected by climate change, we experimentally manipulated temperature in a field study of the wind‐dispersed, invasive plant Carduus nutans (Asteraceae). We quantified seed release in a series of trials conducted in a full‐size experimental wind tunnel, and we examined the effect of the probability of seed release on the projected population spread rate ( c *). Results: Experimental warming over the growing season significantly increased the probability of seed release in wind tunnel trials by 7%. When these data were incorporated into matrix integro‐differential equation models of population spread for this species, the measured increase in seed release, combined with previously reported increases in plant height, resulted in a projected increase in the population spread rate of C. nutans of 38% per year due to increased temperature. Main conclusions: Ignoring altered seed release dynamics significantly underestimates the increase in potential spread rate by 11%. This increase could allow this species to reach suitable habitat more quickly than expected from existing models of population spread, and could require management timing to shift in the future. More generally, our results suggest that models of future distributions of other wind‐dispersed species that do not include information about species' dispersal responses to climate may incur significant errors and could result in poorly applied management or inadequate spatial risk assessment.